The Endogeneity of the Natural Rate of Growth an Empirical Study for Latin-American Countries - Lena Vogel (Hamburg University, Department Economics and Politics, 2007)
The aim of this paper is to analyse the sensitivity of the natural rate of growth to the actual rate of growth for a sample of eleven Latin-American countries, assuming the natural rate to be determined endogenously by changes in the actual rate of growth. The natural rates of growth are estimated in a system of SUR estimations over the period 1986-2003. In order to determine whether they react endogenously to changes in the actual rate of growth, a dummy variable for boom periods is added to the system of regressions. In the second part of the empirical analysis, the direction of causality between input growth and output growth is then tested for four of the countries in the first sample. The results confirm not only the hypothesis about the endogeneity of the natural rate of growth, but also show causality from output growth to input growth to be much stronger than the reverse. Length: 28 pages
Keywords: O40; E10; C23; 330; Natural rate of growth; actual rate of growth; endogeneity; Granger causality; Latin America